THE GROWTH POTENTIAL OF AGRI- AND ECO-TOURISM IN POLAND AS EXEMPLIFIED BY THE SILESIAN VOIVODESHIP - Kaczmarska, Anna (Acta Scientiarum Polonorum. Oeconomia, 2010)
Tourism as an economic activity in an important way influences the natural and anthropogenic environment. Apart from many positive aspects, more and more frequently the negative consequences of its development are observed. Massive, uncontrolled and unsustainable tourism contributes to the emergence of many persistent losses in all components of nature. Nevertheless, there are touristic activities, for example, developed in rural areas, including tourism, which favorably affect the natural environment and all its participants. Still a more interesting solution is promoting sustainable tourism that sustains the ecological, social, infrastructure and economic integrity of the land for present and future generations. Ecotourism, which is the core of sustainable tourism, is currently facing major challenges and, unfortunately, limitations. The paper discusses these aspects as exemplified by Poland with particular reference to the Polish region of Silesia, which to a large extent, is associated with strong industrial and urban degradation. To overcome this stereotype – considering rich resources and environmental qualities of the area – the study has presented the possibilities of developing environmentally friendly tourism.